Impact of COVID-19 lockdown on utilization of massive open online courses among medical students in Tamil Nadu- a cross-sectional study - Kumar, Rakesh; Vignesh, Nawin J.; Bharathi, Mohan; Jawaharlal, Mythili; Mohanty, Milanee; Alfred, Mercy (International Journal Of Community Medicine And Public Health, 2022)
Background: The massive open online courses are one of the blooming and innovative teaching-learning methodologies in the field of medical science. The current study aimed to assess the utilization of massive open online courses among medical students in Perambalur during the COVID-19 lockdown. Methods: The cross-sectional study was conducted among medical students using a structured questionnaire from June 2021 to November 2021. The questionnaire focused on knowledge and perception about MOOC, motivators, and barriers to enrolment in MOOC and the level of satisfaction in MOOC courses. Following assessment, univariate and bivariate analysis of data was performed using statistical software and the results were summarized. Results: The mean age of medical students were 21 years and most of the students were in the first (28.2%) and second year (21.9%). 55.7% of medical students had heard about MOOC and 69.1% of students had enrolled on any one of the online courses. Among those enrolled, 271 students (60.6%) completed the course. The year of study was significantly associated with enrolment to MOOC (p=0.007). The mean age of enrolled students (20.6 years) was lower compared to those not enrolled (20.93 years). Conclusions: The knowledge and perception among medical students about MOOCs were optimal but utilization and course completion were not satisfactory when the students near their undergraduate course completion. Based on government action, it is evident that MOOC will be one of the major teaching-learning methodologies in the near future and this study will serve as a guiding tool to identify the major motivators and barriers to the utilization of MOOC among medical students.